A hardware/software co-design case study on MPEG AAC audio decoder. (27th January 2006) - Tsai, Tsung-Han; Liu, Chun-Nan
This paper presents a hardware/software co-design method for the implementation of AAC audio decoder. We present the approach not only for the characteristics of the algorithm, but also provide the numerical decision for evaluation of the various approaches. The overall system is first analysed and profiled with ARM profiler. Then the decoder system is partitioned into software part and hardware part respectively based on the property of analysis. The software part is developed for the implementation of intensive decision making operations needed for audio bitstreams. The hardware part is a dedicated hardware for the regular and computation-intensive operations in AAC audio decoding.